Are Family Firms Good Employers? - Neckebrouck, Jeroen; Schulze, William; Zellweger, Thomas (Academy of Management Journal, 2018)
Family firms employ about 60% of the global workforce. While it is widely assumed that they are good employers, data about their conduct are mixed. In this study, we extend stewardship and agency theories to test competing propositions about the impact of family on employment practices using data from 14,961 private Belgian firms over a 19-year period. Higher investments, lower dividend payout, and higher risk tolerance indicate that family firms are better financial stewards of their companies than nonfamily firms. However, family firms are worse organizational stewards than nonfamily firms: they offer lower compensation, invest less in employee training, and exhibit higher voluntary turnover and lower labor productivity. Further, and contrary to earlier research, we find that financial practices in private family firms do not change over time, and that the deleterious influence of family on employment practices rises with both firm age and with heightened family involvement. Together, our findings suggest that a more nuanced understanding of stewardship and agency theory is needed to understand the impact of family on the governance of private firms.